Characterization of responder groups to secukinumab treatment in moderate to severe plaque psoriasis. (16th November 2020) - Pinter, Andreas; Gerdes, Sascha; Papavassilis, Charis; Reinhardt, Maximilian
Abstract: Background: Secukinumab is a fully human monoclonal antibody that neutralizes interleukin-17A (IL-17A), a key cytokine involved in the development of psoriasis. Here, we characterized secukinumab treatment-responder profiles and identified baseline factors affecting response. Methods: Pooled phase 3 data from moderate to severe plaque psoriasis patients treated with secukinumab for 16 weeks (FIXTURE [NCT01358578], ERASURE [NCT01365455], and CLEAR [NCT02074982]) were analyzed to characterize responder groups, identifying factors associated with treatment response, and to evaluate early response kinetics as a biomarker for treatment response. Etanercept and ustekinumab were evaluated as comparators. Results: Patients treated with secukinumab 300 mg ( n = 867), ustekinumab 45/90 mg ( n = 318), and etanercept 50 mg ( n = 298) were evaluated. For secukinumab 300 mg, more patients were in higher responder groups than etanercept and ustekinumab. In higher response groups, fewer patients had previous systemic or biologic treatment, metabolic syndrome, hypertension, diabetes, and fewer were current smokers. Mean body weight, waist circumference, and BMI decreased as response level increased. Early onset of response (PASI50 at Week 4 or 8) correlated with sustained efficacy at Week 16. Conclusions: Baseline factors, including weight and cardiometabolic status, were associated with response to secukinumab. Early onset of response may indicate treatment efficacy later on.